Sistem Pakar Diagnosa Penyakit Pernapasan dengan Metode Certainty Factor - Jhondry, Michael; Hansun, Seng (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
Respiratory diseases are illnesses that attacks the respiratory organ system in humans. Unfortunately, the general public does not realize that symptoms such as shortness of breath, coughing and others can become serious illnesses if not treated promptly. Therefore, an expert system designed for early diagnosis of respiratory diseases was developed in this research. The Certainty Factor method is applied in this expert system in the form of a website-based software. From the results of the black box testing, it was concluded that the system can provide accurate diagnosis results. Furthermore, the final evaluation by users using the Technology Acceptance Model yielded a result of 89.21%, showing that the developed system can be accepted by users in diagnosing respiratory diseases effectively.